Fluid structure interface (FSI) of force excitation on pipeline t-joint - Siti Radiah, Arrippin (2013)
This project has been conducted in an attempt to do simulation of pipeline t-joint for the structure itself and for the structure with fluid flow through in it. The first objective of this project are to determine the dynamic characteristic for modal by determining the natural frequency and mode shape of the t-joint by applying impact on the structure. Besides, the second objective is to determine load profile of fluid structure interface (FSI). This thesis conducted experimentally by giving some impact to certain point for the whole structure for three axes, which analyse by programmable computer in order to know the natural frequency and mode shape of the t-joint pipe. This thesis describes ANSYS technique to predict natural frequency, mode shape and fluid structure interface (FSI). The three dimensional solid modelling of tjoint pipeline was developed using the SOLID WORK software. The t-joint pipe analysed using its properties and all the elastic supports that resulting the natural frequency and mode shape. Results obtained in table form and figure from simulation that shows the mode shape and frequency of the t-joint pipe.